Форми діяльності соціально відповідального бізнесу у транскордонному співробітництві країн V-VI розширення ЄС та України - Бутирська, І.В.; Butyrskaya, I.V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The author argues that the CBC member of the fifth and sixth EU enlargement, new forms of activity. Their specificity of action is to enhance socially responsible business. To enter Ukraine into European structures and fruitful collaboration with European partners, it is necessary to take into account the experience of active associations CBC. It is also important to be among the priorities of cooperation between Ukraine and the EU took place some gradual approximation of Ukrainian legislation, norms and standards to European ones.
Forms OF Socially Responsible Business in Сross-border Сooperation of V-VI EU Enlargement and the Ukraine
І.В.Бутирська, к.екон. н., доц. кафедри менеджменту і туризму Чернівецького торговельно-економічного інституту КНТЕУ (Україна, м. Чернівці)
Keywords: Cross-border cooperation; Ukraine; the European Union; Socially Responsible Business